Прогнозування ресурсу трибосистем при використанні сумішевих олив - Журавель, Дмитро Павлович; Журавель, Дмитрий Павлович; Zhuravel, Dmytro; Бондар, Андрій Миколайович; Бондарь, Андрей Николаевич; Bondar, Andrii (My University, 2021)
UK: В статті розглянуто перспективи використання сумішевих олив для мобільних енергетичних засобів. Встановлено, що ефективність змащувального матеріалу визначається, по-перше, конструктивними особливостями вузла тертя, тобто типом, розміром, характером руху поверхонь тертя і т. п. і, по-друге, системою змащування і видом матеріалу, з яким контактує в процесі роботи, а також умовами експлуатації вузла тертя і термінами заміни змащувального матеріалу. Найбільш актуальним напрямком створення нових змащувальних середовищ є використання сумішевих олив мінерального і рослинного походження. Залучення рослинних олив і тваринних жирів, тобто продуктів чисто біосферного походження до складу змащувальних матеріалів слід вважати вельми перспективним. Вони спрямовані на більш ефективне використання продуктів рослинного і тваринного походження в різних областях техніки. Тому використання сумішевих олив з покращеними властивостями є актуальним вирішення питання раціонального використанням їх для забезпечення надійної і ефективної роботи мобільної сільськогосподарської техніки. EN: Тhe article discusses the prospects for the use of mixed oils for mobile energy vehicles. Units and aggregates of functional systems of mobile agricultural machinery are often operated under extreme conditions where the lubrication efficiency can not be achieved by the use of hydrocarbon oils. Only complex synthetic or biological oils with improved properties can have a complex combination of required properties, that is, slight changes in viscosity, high lubricating properties over a wide temperature range, chemical stability, resistance to aging and oxidation. The promising direction of creating new lubricant compositions is the use of alternative types of vegetable base oils, in particular rapeseed oil. The rapeseed oil contains triglycerides, esters and fatty acids: palmitic, stearic, oleic, linolenic, erucic and others, which increase the lubricating ability of the oil under conditions of extreme friction due to the firm adhesion to the metal surface, prevents direct contact with the friction pair. In addition, lubricants should not be biodegraded, do not change their storage and regeneration properties, are easy to transport and do not cause environmental pollution.The structure of the limiting lubricant layers is determined by the physical and chemical properties of the molecules that form the films, and the state and nature of the solid surface. Surfaces may be formed from the lubricant by adsorption, chemisorption or tribochemical reactions. Strong adsorption layers on metals form surface-active substances: fatty acids, their alcohols and esters, animal and vegetable fats, amides, amines and their derivatives of biological oils. Since the formation of films occurs according to the adsorption laws, it depends on the concentration of polar substances in the lubricant and temperature. The efficiency of the lubricant is determined, firstly, by the structural features of the friction unit, that is, the type, size, nature of the motion of the surfaces of friction, and the like. and, secondly, the lubrication system and the type of material that is contacted during the operation, as well as the operating conditions of the friction unit and the dates of the replacement of the lubricant. Therefore, the use of mixing oils with improved properties is an urgent solution to the issue of rational use of them to ensure reliable and efficient work of mobile agricultural machinery. RU: В статье рассмотрены перспективы использования смесевых масел для мобильных энергетических средств. Установлено, что эффективность смазочного материала определяется, во-первых, конструктивными особенностями узла трения, то есть типом, размером, характером движения поверхностей трения и т.п. и, во-вторых, системой смазки и видом материала, с которым контактирует в процессе работы, а также условиями эксплуатации узла трения и сроками замены смазочного материала. Наиболее актуальным направлением создания новых смазочных сред является использование смесевых масел минерального и растительного происхождения. Привлечение растительных масел и животных жиров, то есть продуктов чисто биосферного происхождения в состав смазочных материалов следует считать весьма перспективным. Они направлены на более эффективное использование продуктов растительного и животного происхождения в различных областях техники. Поэтому использование смесевых масел с улучшенными свойствами является актуальным решение вопроса рационального использованием их для обеспечения надежной и эффективной работы мобильной сельскохозяйственной техники.
Forecasting tribosis resources for use of mixtural oils
Прогнозирование ресурса трибосистем при использовании смесевых масел
Keywords: прогнозування; ресурс; трибосистема; сумішеві оливи; присадки; добавки; надійність; сільськогосподарська техніка; forecasting; resource; tribosystems; mixed oils; additives; reliability; agricultural machinery; прогнозирование; ресурс; трибосистемы; смесевые масла; присадки; надежность; сельскохозяйственная техника